ANALISIS YURIDIS KEABSAHAN PERJANJIAN SEWA MENYEWA YANG DITANDATANGANI OLEH PIHAK YANG BUKAN AHLI WARIS (STUDI PUTUSAN MA NO. 798 K/PDT/2014) - NURHABIBAH KEMALA PUTRI (PREMISE LAW JURNAL, 2017)
ABSTRACT As what occurs in the lease certificate according tothe Supreme Court’s Ruling No. 798 K/Pdt/2014, the signing of leasing agreement embodied in the Leasing Contract is done before Notaries in Medan. The research problems are formulated as follows: how about the validity of Leasing Contract signed by those who are not heirs, how about Notary’s liability for a leasing contract, how about juridical analysis on leasing contract signed by those who are not heirs in the Supreme Court’s Ruling No. 798 K/Pdt/2014. The research used juridical normative or doctrinal law method. The data were analyzed qualitatively in which important data were analyzed whilethe unimportant ones were eliminated, and the conclusion was drawn by using deductive-inductive method. Keywords: Validity of Contract, Leasing Contract, Signature, Heir